2011
DOI: 10.4149/neo_2011_03_251
|View full text |Cite
|
Sign up to set email alerts
|

Association of Toll like receptor 9 expression with lymph node metastasis in human breast cancer

Abstract: The toll like receptor 9(TLR9) has been suggested to play an important role in the invasion and metastasis of cancer cells in vitro. However, the expression of TLR9 in human cancer specimens has never been characterized. In this study, we investigated the expression of TLR9 in breast cancer specimens and determined the association between its expression and the clinicopathological features observed. We found that TLR9 expression was significantly higher in patients with breast cancers displaying large tumor si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
0
9
1
2
Order By: Relevance
“…For example, recognition of self-DNA/protein complexes by TLR9 mediates pDC activation in psoriasis, breaking self-immune tolerance (24). Members of the TLR family, including TLR9, are often ectopically expressed in tumors (39, 40), can induce tumor invasion in vitro (41), and may be an indicator of poor prognosis in vivo . Similarly, expression of TLR9 has been found to correlate with the invasive and metastatic potential of pancreatic carcinoma (42).…”
Section: Discussionmentioning
confidence: 99%
“…For example, recognition of self-DNA/protein complexes by TLR9 mediates pDC activation in psoriasis, breaking self-immune tolerance (24). Members of the TLR family, including TLR9, are often ectopically expressed in tumors (39, 40), can induce tumor invasion in vitro (41), and may be an indicator of poor prognosis in vivo . Similarly, expression of TLR9 has been found to correlate with the invasive and metastatic potential of pancreatic carcinoma (42).…”
Section: Discussionmentioning
confidence: 99%
“…These signaling pathways are all involved in pathways expressing various types of pattern recognition receptors (PRRs). Recently, many studies have confirmed that glioma, breast, prostate, lung, ovarian and esophageal cancer cells are all related to the 'Toll-like receptor signaling pathway' (28)(29)(30)(31). These studies used microorganism-derived TLR ligand to indicate that the TLR expressed in the tumor cells had functional activities (32).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2 expression has been found increased in gastric cancer cells125 and CRC 171. MMP-9 was shown to be expressed in many cancer cells, including those associated with NSCLC,172 lymph node metastasis in human breast cancer,173 ovarian cancer invasion and metastasis,174 glioblastoma multiforme,175 and adamantinous craniopharyndioma 176. The secretion of MMP-2 and MMP-9 by leukemic cells increased the permeability of the blood–brain barrier of the central nervous system by disrupting tight junction proteins 177.…”
Section: The Role Of β-Adrenergic Blockers In Cancermentioning
confidence: 99%